Detecting Canada : essays on Canadian crime fiction, television, and film - Rose, Marilyn J; Sloniowski, Jeannette, 1946- (Film + media studies., 2014)
This book-length study of crime writing in Canada, Detecting Canada, contains thirteen essays on many of Canada's most popular crime writers, including Peter Robinson, Giles Blunt, Gail Bowen, Thomas King, Michael Slade, Margaret Atwood, and Anthony Bidulka. Genres examined range from the well-loved police procedural and the amateur sleuth to those less well known, such as anti-detection and contemporary noir novels. The book looks critically at the esteemed sixties' television show Wojeck, as well as the more recent series Da Vinci's Inquest, Da Vinci's City Hall, and Intelligence, and the controversial Durham County, a critically acclaimed but violent television series that ran successfully in both Canada and the United States. The essays in Detecting Canada look at texts from a variety of perspectives, including postcolonial studies, gender and queer studies, feminist studies, Indigenous studies, and critical race and class studies. Crime fiction, enjoyed by so many around the world, speaks to all of us about justice, citizenship, and important social issues in an uncertain world.